PENINGKATAN PRESTASI BELAJAR MATEMATIKA TENTANG FPB DAN KPK MELALUI METODE TUGAS DENGAN LKS - Sugiarti, Erlin (WAHANA PEDAGOGIKA, 2016)
The purpose of the study was to (1) improve the learning achievement of mathematics and (2) get a way or method that can improve the studentsâ achievement in mathematics learning material about the FPB and KPK. The study was conducted using classroom action research design and was divided into two cycles. Each cycles consisted of four stages: (1) improvement plan, (2) Implementation of improvement, (3) observation, and (4) reflection. The study was conducted in the first state elementary school of Sukolilo, Sukodadi, Lamongan with subject improvements was the fourth graders. The results of the study in the first cycle indicated that the students had not mastered the material primarily determines the FPB. While on the second cycle it was no longer visible, because the application of the method with LKS tasks could improve the learning achievement of mathematics. The students quickly respond, or respond to, especially for children to think fast that in working on the next task the stdudentsâ abilities increased. From these results it could be concluded that the implementation of the task of LKS method could improve the forth gradersâ achievement at the first state elementary school of Sukolilo on the material of FPB and KPK.